Evaluation of inherent safety strategies using FAHP to reduce human error - Abdul Wahab, N. (Trans Tech Publications Ltd, 2014)
Inherent safety concept has been introduced to overcome the shortcoming of traditional hazard assessments by allowing modification to be made at any stage of lifecycle of a process plant. However, most of the proposed inherent safety modifications were suitable to prevent fire, explosion and toxic hazards assessment but less attention on human and organizational factor. Therefore, this paper introduces the inherently safer analysis for human and organizational factor to be implemented during design stage or process operation. Analytic Hierarchy Process model integrated with fuzzy logic and known as FAHP was employed to rank identified inherently safer strategies. The model was applied to select inherently safer strategies to reduce collision risk of a floating production, storage and offload and the authorized vessel. The result shows that minimization of hazardous procedure when the procedure is unavoidable is the best strategy to increase human performance. It is proven that the proposed methodology is capable to select the inherently safer strategy without requiring a bunch of precise information to transfer expert judgment in human performance's perspective. Â© (2014) Trans Tech Publications, Switzerland.